Effects of metoclopramide-induced hyperprolactinemia on the prolactin and prolactin receptor expression of murine adrenal. (2nd December 2015) - do Amaral, Vinícius Cestari; da Silva, Priscilla Ludovico; Carvalho, Kátia Candido; Simoncini, Tommaso; Maciel, Gustavo Arantes Rosa; Soares-JR, José Maria; Baracat, Edmund Chada
Abstract: The aim of this study was to evaluate the effects of metoclopramide-induced hyperprolactinemia on the prolactin (PRL) and prolactin receptor's (PRLR) expression in the adrenal. For this purpose, a total of 12 animals with intact ovaries were allocated to two groups: G1 (saline solution) and G2 (metoclopramide). A total of 30 oophorectomized animals was randomized to five subgroups: G3 (saline solution), G4 (metoclopramide), G5 (metoclopramide + 17β-estradiol), G6 (metoclopramide + progesterone), and G7 (metoclopramide + 17β-estradiol + progesterone). Immunohistochemical analyses were evaluated semi-quantitatively. For PRLR, the area fraction of labeled cells (ALC) varied from 1 (0–10%) to 3 (> 50%). Based on the mean of the immunostaining intensity, G2 and G4 showed strong expression; G6 and G7 presented a mild reaction; and G1, G3, and G5 exhibited a weak reaction. Concerning PRL, the ALC varied from 1 (0–10%) to 3 (> 50%), and groups G6 and G7 showed a strong reaction; G2, G4, and G5 showed a mild reaction; and G1 and G3 exhibited a weak reaction. These findings suggest that metoclopramide-induced hyperprolactinemia increases PRL expression in the adrenal glands of mice. Furthermore, progesterone alone or in association with estrogen also increases PRL expression, but to a lesser extent.